The Psychological Rehabilitation impact through Dohsa-Hou Method on Motional Performance and Peers Relationship Self-Efficacy of Children suffering from Attention Deficit Hyperactivity Disorder (ADHD) - kordi Tamandani, Farzaneh; Rigi Kooteh, Behzad; Mehrpoor, Zahra (International Journal of Applied Behavioral Sciences, 2015)
Introduction: The aim of the present research was to study the psychological rehabilitation impact through Dohsa-Hou on motional performance and peer relationship self-efficacy of children suffering from ADHD at Zahedan City. Methods: The research is semi-experimental including pre-test, post-test and follow-up in two experiment and control groups. The research statistical population includes all children suffering from ADHD. 30 children 7-9 suffering from ADHD was selected through sampling. 15 children were assigned in control group and 15 children were assigned in experiment group randomly. Furthermore, another assessment was conducted through post-test and follow-up at the end. Dohsa-Hou treatment duration was 12 sessions in experiment group (3 sessions per week) and follow-up was conducted one week after the post-test. Data resulted from questionnaire were analyzed using SPSS-19 software and descriptive and inferential tests. Results: The results of analysis MANCOVA showed that psychological rehabilitation through Dohsa-Hou method has caused to increased motional performance and self-efficiency promotion of children suffering from (ADHD) in relationship with their peers (P≤0.01). Conclusion: Dohsa-Hou method is an effective treatment for promotion of their motional performance and self-efficiency in relationship with their peers. Declaration of Interest: None